Carpentier-Edwards Magna Ease bioprosthesis: a multicentre clinical experience and 12-year durability. (28th December 2021) - Piperata, Antonio; Fiocco, Alessandro; Cavicchiolo, Andrea; Ponzoni, Matteo; Pesce, Rita; Gemelli, Marco; Evangelista, Giuseppe; Gastino, Elisa; Michelotti, Sara; Mazzaro, Enzo; Garufi, Luigi; DePaulis, Ruggero; et al.
Abstract: OBJECTIVES: The goal of this multicentre retrospective study was to compare long-term clinical and haemodynamic outcomes of the Carpentier-Edwards Magna Ease (CEME) bioprosthesis by patient age. METHODS: We included consecutive patients who underwent isolated and combined surgical aortic valve replacement (AVR) with CEME valve between January 2008 and March 2020 at 4 cardiac surgery centres in Italy. Survival distribution was evaluated at follow-up according to age and surgery type (combined or isolated AVR), together with freedom from structural valve deterioration (SVD), reoperation and combined events, i.e. SVD, reoperation, endocarditis and thromboembolic events. RESULTS: A total of 1027 isolated and 1121 combined AVR were included; 776 patients were younger than 65 years whereas 1372 were 65 years or older. The 30-day Valve-Academic-Research-Consortium mortality was 2% (<65 years) and 6% (≥ 65 years) ( P < 0.001), whereas it was 3% for isolated AVR and 7% for combined AVR ( P < 0.001). The 12-year survival was 81% for those younger than 65 years vs 45% for those equal to or older than 65 years ( P < 0.001), whereas they were 61% vs 49% for isolated and combined AVR ( P = 0.10). The 12-year freedom from combined events, excluding death, was 79% for those younger than 65 years vs 87% for those equal to or older than ( P = 0.51), whereas they were 83% for isolated and 86% for combined AVR ( P = 0.10). The 12-year freedom from SVD was 93% and 93% in patients younger than 65 and those equal to or older than 65 years ( P = 0.63), and the results were comparable even in cases with isolated and combined AVR (92% vs 94%, P = 0.21). A multivariable Cox analysis including gender, presence of patient–prosthesis mismatch, isolated AVR and age showed that only the age was an independent risk factor for the incidence of SVD ( P = 0.029). CONCLUSIONS: Outcomes from this large multicentre analysis demonstrated that a CEME bioprosthesis provides good clinical results and long-term durability even in patients younger than 65 years. Furthermore, the hazard for SVD has been shown to be lower for older age. Clinical trial registration number: 105n/AO/21. Abstract : Surgical aortic valve replacement (SAVR) is an excellent option for patients with severe aortic valve disease.